MENINGKATKAN PENGETAHUAN TENTANG AKADEMISI MELALUI SOSIALIASI PADA MASYARAKAT DI LAMPUNG - Yuniar Sari; Ridwansyah Ridwansyah; Erike Anggraeni (LPPM Universitas Bina Bangsa, 2024)
An academic is someone who works at a university, institute, or other educational institution. This dedication to the community is aimed at providing knowledge to the public about academics. The method used in this activity consists of three stages: planning, implementation, and evaluation. The activities are delivered through the method of lectures and joint discussions after lectures. The results of these activities show that active collaboration between academics and society enables the exchange of knowledge, expertise, and resources to create innovations that meet the needs of society. The importance of understanding the needs and aspirations of local communities in the process of developing solutions is also at the heart of this research. This activity contributes to the public's understanding of academics